A joint optimization algorithm based on energy efficiency maximization for massive MIMO systems - Haiyan CAO; Ruirui FENG; Xin FANG; Xiumin WANG; Fangmin XU (Dianxin kexue)
For the massive multi-cell multi-input multiple-output (MIMO) communication uplink system with unknown channel status information,a resource allocation algorithm which jointly optimizes the pilot sequence length,pilot symbol power and data symbol power was proposed.With the maximum ratio combining (MRC) receiver,the influence of circuit power was considered,pilot contamination and the constraint of maximum transmission power,and a nonconvex function modeled with the goal of maximizing energy efficiency (EE) was established.Firstly,the fractional form was transformed into an equivalent subtractive form by using the properties of fractional programming and then decomposed into a series of DC problems,finally,by using an iterative optimization algorithm,the three variables were alternately adjusted with maximizing the energy efficiency.Simulation results show that with the increasing of the maximum symbol transmission power,the proposed scheme can still have the great EE performance for the massive MIMO systems.